The effect of Aspalathin linearis, Cyclopia intermedia and Sutherlandia frutescene on sperm functional parameters of healthy male wistar rats - Omolaoye, Temidayo S.; Skosana, Bongekile T.; du Plessis, Stefan S. (Frontiers in Physiology, 2023)
Rooibos (Aspalathin linearis), honeybush (Cyclopia intermedia), and sutherlandia (Sutherlandia frutescene) are three Southern Africa indigenous plants, of which the extracts have become house-hold items and are consumed on a large scale. Although, they are known for their antioxidant properties, studies have highlighted danger in the excessive intake. Therefore, the current study investigated whether treatment with rooibos, honeybush, and sutherlandia will impact sperm functional parameters positively or otherwise, in healthy rats. Fourteen-week-old pathogen-free adult male Wistar rats (250-300g) were randomly divided into four groups of ten, including a control, rooibos (RF), honeybush (HB) and a sutherlandia (SL) group. After seven weeks of treatment, animals were sacrificed. Spermatozoa were retrieved from the cauda epididymis for motility, morphology and concentration analysis and the testis was used for all biochemical assays. The infusion treated animals (RF, HB, and SL) presented with a non-significant decrease of -14.3%, -18.2%, -17.2% and -24.8%, -20.7%, -27.3% in total motility and progressive motility when compared to the control group respectively. There was a significant increase in number of spermatozoa with slow speed (P=0.03), especially in SL treated group compared to the control (P=0.03). Additionally, there was an increase of 28.8%, 31.7%, 23% in superoxide dismutase (SOD) activity of RF, HB and SL compared to control respectively. This was accompanied with a percentage decrease of -21.1%, -23.7%, 45.9% in malondialdehyde (MDA) levels compared to the control group. In summary, animals treated with the respective infusions presented with a percentage increase in SOD activity but have reduced sperm motility and decreased normal morphology. Paradoxically, they presented with increased sperm concentration. Hence, it is presumed that rooibos, honeybush and sutherlandia may enhance sperm quantity (concentration) but may impair sperm quality (motility morphology) when consumed by healthy animals.